2012
DOI: 10.1007/s10549-012-2311-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, performance status, cancer activity, and IL-6 on anxiety and depression in patients with metastatic breast cancer

Abstract: Depression and anxiety are the core disorders causing emotional distress in patients (pts) with metastatic breast cancer. The aim of our study was to screen metastatic breast cancer outpatients for anxiety and depression, and to investigate the influence of age, Karnofsky Performance Status (KPS), cancer activity, and inflammation as represented by IL-6 levels on these two mood disorders. Pts treated with chemotherapy for metastatic breast cancer (n = 70) were assessed using the Hospital Anxiety and Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 30 publications
3
41
1
2
Order By: Relevance
“…The impact of other previously identified socio-demographic predictors404142, such as age, gender and marital status, were not confirmed in our study. These inconsistencies may arise from differences in patient populations, statistical methodology, and measured symptom domains.…”
Section: Discussioncontrasting
confidence: 99%
“…The impact of other previously identified socio-demographic predictors404142, such as age, gender and marital status, were not confirmed in our study. These inconsistencies may arise from differences in patient populations, statistical methodology, and measured symptom domains.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with previous studies (Burgess et al, 2005; Hartl et al, 2010; Hong and Tian, 2014; Jehn et al, 2012; Linden et al, 2012; Parker et al, 2007; Thomas et al, 2010), patients with Higher Anxiety and Subsydromal Depression were younger than women with neither symptom. As noted in two previous reviews (Compas et al, 1999; Mosher and Danoff-Burg, 2005), a number of factors may explain these age-related differences.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, higher depressive symptoms related to less benefit finding, and higher anxiety related to more financial concerns. Depression and anxiety are prominent concerns for MBC patients [1316]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of MBC patients report high levels of depressive symptoms [13, 14] and anxiety [15, 16]. One study demonstrated that 33% of MBC patients evidenced clinical levels of depression via diagnostic interviews [17].…”
Section: Introductionmentioning
confidence: 99%